Devil's peak [videorecording (DVD)] - Knott, Robert, 1954-; Haley, Jackie Earle, 1961-; Penn, Hopper, 1993-; Thornton, Billy Bob; Wright, Robin, 1966-; Joy, David, 1983- (Screen Media, 2023)
An Appalachian crime lord controls his family and his meth business with his fists. When his son meets the girl of his dreams, desperately wanting to escape the life he is expected to lead and free himself from the clutches of his father, he is forced to go head-to-head with the terrifying man who will stop at nothing to ensure loyalty from all of those around him.